THE JIHAD OF ECONOMIC: THE SPIRIT OF ISLAMIC ECONOMIC MOVEMENT BY KYAI IN MADURA - Zainal Abidin (Share: Jurnal Ekonomi dan Keuangan Islam, 2015)
The dynamics that occur in the business by kyai in Pamekasan is dynamic in the whole side of the boarding school like the actors, software, and hardware of a boarding school, where the kyai as a determinant factor of the dynamics including the dynamics of business. Kyai and the boarding school do the business can be differentiated into three types, namely: kyai of business, a boarding school of business, and kyai and boarding school of business. It was implemented in a manner that istiqamah, consistent, resignation and exert all the ability to get kosher profits according to shariah. The spiritual value of business by kyai is the crystallization of ‘aqidah, shariah, and akhlaq which is based on Al-Quran and Al-Sunnah, which includes economic jihad, 'iffah and businesses as a movement of da’wah namely da’wah bi al- hal as a basic. Kyai who do the business is able to meet all levels of the hierarchy of needs ranging from physiological needs to self-actualization needs of kyai as a personal of himself as well as leaders of boarding schools, so kyai be independent to do everything according to Kyai’s idealism without intervention from the other. =========================================== Dinamika yang yang terjadi dalam bidang bisnis oleh kyai di Pamekasan adalah dinamika di seluruh sisi pesantren yang seperti para pelaku, perangkat lunak dan perangkat keras sebuah pesantren, dimana kyai sebagai faktor penentu dinamika termasuk dinamika bisnis. Kyai dan pesantren melakukan bisnis yang dapat dibagi menjadi tiga tipe, yaitu: bisnis kyai, bisnis pesantren, dan kyai dan pesantren bisnis. Hal ini diimplementasikan secara istiqamah, konsisten, dikenal dan digunakan pada seluruh kemampun untuk mendapatkan keuntungan yang layak sesuai dengan syari’ah. Nilai spiritual dalam bisnis oleh kyai adalah kristaliasi dari ‘aqidah, syari’ah dan akhlak yang berdasarkan Al Qur’an dan Al Sunnah, termasuk ekonomi jihad, ‘iffah dan bisnis sebagai suatu gerakan dakwah yang disebut dengan da’wah bi al- hal sebagai dasarnya. Kyai yang melakukan bisnis mampu berhadapan dengan semua tingkatan hierarki kebutuhan dimulai dari kebutuhan psikologis, hingga kebutuhan aktualisasi diri kyai sebagai pribadi dan juga sebagai pemimpin pesantren, maka kyai dapat bebas melakukan segala sesuatu menurut idealism kyai tanpa adanya intervensi dari pihak lain.